2013
DOI: 10.1638/2012-0144r1.1
|View full text |Cite
|
Sign up to set email alerts
|

ESTIMATION OF NORMAL TEAR PRODUCTION IN FREE-LIVING EURASIAN BLACK VULTURES (AEGYPIUS MONACHUS) AND GRIFFON VULTURES (GYPS FULVUS) IN DADIA NATIONAL PARK, GREECE

Abstract: The aim of this study was to record the Schirmer tear test I (STT I) measurements in free-living vultures in order to estimate normal values. The Eurasian black vulture (Aegypius monachus), which breeds in the Mediterranean region and Asia, is listed as near threatened; it is also classified as vulnerable at the European level and endangered in Greece. The griffon vulture (Gyps fulvus), once widespread across the continent, has undergone a dramatic decline which has led to its extinction in many regions. Sixty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…18 The effect of age was not assessed in this study because precise determination of age was not possible in our study population. In Humboldt penguins, 7 macaroni penguins, 8 rockhopper penguin, 8 Screech owls, 10 vultures, 12 ostriches, 13 and American flamingos, 21 the age and gender did not alter results of STT and/or IOP in studied animals. But as determined by Reuter and colleagues in some birds of prey (northern goshawks, common buzzards, and common kestrels), 18 younger birds had lower IOP values than did older birds.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…18 The effect of age was not assessed in this study because precise determination of age was not possible in our study population. In Humboldt penguins, 7 macaroni penguins, 8 rockhopper penguin, 8 Screech owls, 10 vultures, 12 ostriches, 13 and American flamingos, 21 the age and gender did not alter results of STT and/or IOP in studied animals. But as determined by Reuter and colleagues in some birds of prey (northern goshawks, common buzzards, and common kestrels), 18 younger birds had lower IOP values than did older birds.…”
Section: Discussionmentioning
confidence: 76%
“…17 Estimation of normal tear production is an essential tool for the identification of ocular surface diseases in any species. 12 The Schirmer tear test, modified Schirmer strips, and phenol red thread test have been used in different avian species to measure aqueous portion of tear film. Williams (1994) reports Schirmer tear test results of 8 AE 1.5 mm (mean AE SD) in large Psittaciformes such as African gray parrots (Psittacus erithacus) and 4.5 AE 1 mm in small species such as lories and conures.…”
Section: Discussionmentioning
confidence: 99%
“…25 Therefore, a reason for absence of dazzle in the flamingos is difficult to postulate. We used the brightest setting on a light source available from 7 ; however, the assessment of a dazzle reflex is sporadically reported in other avian species. The remainder of the neuro-ophthalmic examination was consistent with findings of other published reports in avian species, with only the direct pupillary light reflex being observed.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Mean tear production as measured by the mSTTI in our study was 12 mm/min; this value was higher than the mean tear measurement by STTI in most other bird studies, though values ranging from ,2 mm/min to over 16 mm/min have been reported. [2][3][4][5][7][8][9][10][11] Most of these other studies used an unmodified, standard STTI strip; direct comparison could be hindered by the modification of the test strip, which resulted in decreased surface area of the filter paper for litmus effect. Only one of these previously published studies 11 used the same modification of the STT strip in tawny owls; mean tear production was much lower in that group of birds at 3.2 mm wetting per minute, as compared with our group of flamingos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation